People telling stories - Sonya Sherman (Archives & Manuscripts, 2014)
There are stories that take seven days to tell... there are other stories that take you all your life... The truth about stories is that that’s all we are. (Thomas King)1In the late-1980s and early-1990s, some amazing things happened in archives and records theory. Confronted by the rise of electronic records and a challenge to re-imagine accepted models, some clever people did just that.